The Persistence of Presentism - Hargreaves, Andy; Shirley, Dennis (Teachers College record (1970), 2009)
Background/Context: This study draws on the voluminous research on teachers' workplace orientations and especially on Dan Lortie's documentation of conservatism, individualism, and presentism among teachers. Purpose/Objective/Research Question/Focus of Study: This study investigated a school reform network of over 300 secondary schools entitled Raising Achievement Transforming Learning (RATL) to explore the role of the network's interventions in increasing or diminishing presentism. Setting: England. Population/Participants/Subjects: Quantitative performance data were analyzed for all 300 schools. Site visits were made to 10 RATL schools in which educational administrators and teachers were interviewed individually and in focus groups. Additional phone interviews were conducted with administrators in 14 RATL schools. Intervention/Program/Practice: RATL provided a combination of interventions and supports for schools in the network, including data analysis and capacity enhancement; partnering mentor schools with low-performing schools; regional conferences; a Web portal for schools in the project; and a menu of short-, medium-, and long-term strategies for change. Research Design: Qualitative interviews and focus groups of educators in RATL schools, along with secondary analysis of pupil performance data. Conclusions/Recommendations: In Dan Lortie's seminal research on teachers' workplace orientations, he identified "presentism," or short-term thinking, with conservatism and individualism. This research indicates that in the RATL project, individualism among teachers diminished, but this did not diminish either conservatism or presentism. The research identifies three kinds of presentism--endemic, adaptive, and addictive--that have amplified educational conservatism while altering its nature to fit the current culture and political economy of fast capitalism.